Pfeiffer syndrome type I : A case report - Pravita, Dita Juliana; Sari, Dinda Nawang; Asy’ari, Maulfi Natsir; Wardani, Khairunnisa (JKKI : Jurnal Kedokteran dan Kesehatan Indonesia, 2025)
Pfeiffer syndrome is a rare genetic disorder characterized by various congenital anomalies such as brachycephaly, syndactyly, and craniosynostosis. This syndrome is a rare condition with a prevalence of 1 in 100,000 births. This case report discusses a seven-day-old female infant referred to dr. Soediran Mangun Sumarso Regional General Hospital, Wonogiri, Central Java, Indonesia, with Pfeiffer syndrome type 1 due to various physical abnormalities, including brachycephaly, hand and foot anomalies such as brachydactyly, syndactyly, and additional varus deformities in both feet, without any family history of similar disorders. The diagnosis of this case was made through physical examination and postnatal supporting tests. Although the prognosis for this patient is poor due to significant physical abnormalities and decreased neurological development, the outcome may still be better compared to patients with Pfeiffer syndrome types 2 and 3. The limited availability of genetic testing facilities in Indonesia hinders a more comprehensive diagnosis. Genetic testing of both parents is recommended to anticipate the risk of genetic inheritance in future pregnancies. To our knowledge, this is the first case reported in Wonogiri, Indonesia. Awareness and early detection by medical personnel play a crucial role in managing Pfeiffer syndrome, considering the rarity, complexity, and clinical variability of this condition.